Pengaruh Maturity, Peringkat Obligasi, dan Debt to Equity Ratio terhadap Yield to Maturity Obligasi - Novi Dayanti; Janiman Janiman (Universitas Swadaya Gunung Jati, 2019)
Bonds are a long-term contract in which the borrower agrees to make interest and principal payments on the due date. Bonds offer a yield (rate of return) for investors. One measure of the yields most often used by investors in investing is yield to maturity. Yield to maturity is the compounded rate of return that investors will receive if they buy bonds at current market prices and hold the bonds to maturity.The purpose of this research is to analyze the influence of maturity, bond rating and debt to equity ratio on yield to maturity of corporate bonds. This research is a basic research using associative method with quantitative approach The research population is all corporate bonds are listed on BEI in 2014-2017. Sample selection in this research using purposive sampling method. The sample used in this research is 30 companies with the number of bonds issued as many as 87 bonds for the year 2014-2017. Data analysis method used in this research is multiple linear regression analysis with hypothesis testing using SPSS 23 for windows program. The results shows that maturity and bond rating affect the yield to maturity of bonds while debt to equity ratio does not affect yield to maturity of bonds. Suggestions for further research is adding to the researchers period and adding other variables that may affect the yield to maturity of bonds.